2007
DOI: 10.1063/1.2404786
|View full text |Cite
|
Sign up to set email alerts
|

Stability of 3C-SiC surfaces under diamond growth conditions

Abstract: The present study deals with the interaction of C-terminated c(2×2) and Si-rich 3×2 3C-SiC (100) reconstructed surfaces with a microwave plasma chemical vapor deposition used for diamond growth. Pure hydrogen and hydrogen/methane exposures have been carried out. Their effects on the atomic ordering and the stoichiometry within the first planes have been studied in situ using low energy electron diffraction and electron spectroscopies: x-ray photoelectron spectroscopy, x-ray Auger electron spectroscopy, and ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
2
13
0
Order By: Relevance
“…At the same time, XPS revealed the presence of oxygen at the surface after the CVD exposure, the XPS C 1s/O 1s area ratio is 5.7. This value is close to the one previously measured on C-terminated surfaces after comparable plasma treatment [4]. The binding energy shift disappeared as the oxygen was desorbed after annealing at 1050°C (not shown).…”
Section: A U T H O R ' S P E R S O N a L C O P Ysupporting
confidence: 74%
See 3 more Smart Citations
“…At the same time, XPS revealed the presence of oxygen at the surface after the CVD exposure, the XPS C 1s/O 1s area ratio is 5.7. This value is close to the one previously measured on C-terminated surfaces after comparable plasma treatment [4]. The binding energy shift disappeared as the oxygen was desorbed after annealing at 1050°C (not shown).…”
Section: A U T H O R ' S P E R S O N a L C O P Ysupporting
confidence: 74%
“…However, these mechanisms can not be invoked in our study because i) the surface stoichiometry, as determined by XAES, clearly demonstrated a carbon enrichment and ii) our previous experiments [4] showed that the etching by H 2 plasma is negligible for C-terminated 3C-SiC surfaces. Therefore, the formation of anisotropic stripes seems related to atomic surface diffusion processes activated by bombardment of ions with suitable kinetic energy.…”
Section: Discussion and Summarymentioning
confidence: 86%
See 2 more Smart Citations
“…[12] This is in fair agreement with the Full Paper XAES C KVV/Si LVV ratio close to that of the C-terminated c(2 Â 2) reconstructed surface. [13] The surface analysis is completed by ex-situ HREELS investigations after annealing at 573 K to desorb contaminants. HREELS is a powerful technique for probing the surface bonds, especially those involving hydrogen.…”
Section: Surface Modifications Occurring During Pepsmentioning
confidence: 99%